2012
DOI: 10.1007/s00431-012-1731-7
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of risk factors for severe hand–foot–mouth disease among children in Ningbo, China, 2010–2011

Abstract: Clinicians should pay increased attention to children diagnosed as HFMD with the independent risk factors above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
4
32
3
Order By: Relevance
“…Notably, myoclonic jerks (100% in cases and 0 in controls) presented during the early stage of onset of severe HFMD, which is easily identifiable and can be used as an early sign to predict central nervous system (CNS) involvement. Chong et al reported that vomiting may be a signal indicating CNS involvement [19], whereas Yang et al showed that leg trembling was associated with severe HFMD [13]. In our study, vomiting occurred in 23.1% of the severe cases and 5.4% of the mild HFMD, and only 12.3% of the severe cases exhibited leg trembling.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Notably, myoclonic jerks (100% in cases and 0 in controls) presented during the early stage of onset of severe HFMD, which is easily identifiable and can be used as an early sign to predict central nervous system (CNS) involvement. Chong et al reported that vomiting may be a signal indicating CNS involvement [19], whereas Yang et al showed that leg trembling was associated with severe HFMD [13]. In our study, vomiting occurred in 23.1% of the severe cases and 5.4% of the mild HFMD, and only 12.3% of the severe cases exhibited leg trembling.…”
Section: Discussioncontrasting
confidence: 43%
“…In addition, the severe cases presented a high proportion of complications for brainstem encephalitis, neurogenic pulmonary edema and sepsis. These results may be attributed to the higher number of EV71 positive cases compared to the controls [13]. Previous studies indicated that EV71 is more likely to cause serious complications than other enteroviruses and usually leads to brainstem encephalitis, neurogenic pulmonary edema, and circulation failure [14][16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1,4 Considering that an ulcer is the remnant of a ruptured vesicle, the absence of oral ulcers being related to fatal HFMD is similar to our results. Free EV or infected leukocytes localizing in the small blood vessels is the prerequisite of a lesion in the skin or mucosa.…”
Section: Discussionsupporting
confidence: 93%
“…have been found to be related to severe neurological complications or death in hand, foot, and mouth disease (HFMD). [1][2][3][4] Our study indicates that the absence of exanthema was related to death and illness severity in children with acute EV infection in Guangdong Province, China during 2009-2012. Significantly higher percentages of death (7.2% vs. 1.1%; p = 0.001), severe CNS involvement + CPF (9.6% vs. 2.3%; p = 0.025), severe CNS involvement (21.7% vs. 11.0%; p = 0.005), CNS involvement (41.0% vs. 31.0%; p = 0.041), altered level of consciousness (15.7% vs. 7.6%; p = 0.013), convulsions (14.4% vs. 6.3%; p = 0.007), and fever !3 days (67.5% vs. 56.1%; p = 0.048) were found in the group of patients without exanthema compared to the group of patients with exanthema (Table 1).…”
Section: Discussionmentioning
confidence: 82%